(untitled) (Journal of Asian Development Studies, 2013)
The purpose of this article is to describe the interesting and fast development of the textile industry in Faisalabad. Faisalabad was a small town which was known as Lyallpur at the time of independence in 1947 and had few small industrial units. But immediately after independence it made speedy progress and establish a strong viable industrial base to support the economy of the city and Pakistan. The major development in industrial sector was made in the textile industry. Today this textile industry is occupied second position after Karachi in the country as for as number of textile units are concerned. Many of the textile firms in the country are clustered in Faisalabad region and are successfully competing in distant local and International markets. The textile industry is the backbone of Faisalabad’s economy therefore it’s called the “city of textile”. Its role in Pakistan’s economy is also vital as it is the leading producer of cotton that provides the basis for clothing and textile industry development. Due to rapid development of textile industry in the city it is recognized as the ‘Manchester of Pakistan’. In the article, ‘origin of textile industry in Faisalabad,’ an attempt is made to describe the story of development of textile industry and its role in socioeconomic development of the city as well as of the country. A great number of weaving units of power looms can be seen at small distances in Faisalabad. Historical research methodology was used. The data was collected from some primary sources and some from secondary sources and analyzed. In this paper to support historical methodology critical analysis of the content is made.